2007
DOI: 10.3354/meps07088
|View full text |Cite
|
Sign up to set email alerts
|

Springtime transport and retention of Calanus finmarchicus in Massachusetts and Cape Cod Bays, USA, and implications for right whale foraging

Abstract: The Massachusetts Bay (MB) and Cape Cod Bay (CCB) system is a unique coastal embayment, with CCB serving as a high-use feeding ground for endangered North Atlantic right whales Eubalaena glacialis during winter and early spring. We used a hydrodynamic model, observed Calanus finmarchicus (the preferred prey of right whales) abundance, and right whale sightings during 1997-2004 to examine the transport and retention of C. finmarchicus in MB-CCB and the implications for right whale activity. A particle-tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…Pendleton et al (2009) (2006) found an association between right whales and zooplankton abundance, with variability in wind-driven currents playing a dominant role in determining plankton abundance. Particle tracking simulations support the assertion that circulation variability strongly influences copepod abundance and right whale feeding conditions, especially in coastal habitats (Jiang et al 2007). Kenney et al (2001) considered how the sensory mechanisms and foraging strategies used by right whales could change across spatial scales.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Pendleton et al (2009) (2006) found an association between right whales and zooplankton abundance, with variability in wind-driven currents playing a dominant role in determining plankton abundance. Particle tracking simulations support the assertion that circulation variability strongly influences copepod abundance and right whale feeding conditions, especially in coastal habitats (Jiang et al 2007). Kenney et al (2001) considered how the sensory mechanisms and foraging strategies used by right whales could change across spatial scales.…”
Section: Discussionmentioning
confidence: 62%
“…and Centropages typicus are important prey during this period (Mayo & Marx 1990, DeLorenzo Costa et al 2006). As C. finmarchicus abundance increases in early spring, increasing numbers of this species are transported into coastal regions like Cape Cod Bay (DeLorenzo Costa et al 2006, Jiang et al 2007), and C. finmarchicus becomes a larger component of the right whales' diet. Even though C. finmarchicus abundance increases in the spring in Cape Cod Bay, the abundance is even higher in deeper habitats (Meise & O'Reilly 1996) and right whale sightings in Cape Cod Bay begin to decline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calanus finmarchicus exhibited a precipitous drop from 2000 to 2001, followed by a sharp ascent in 2002 to maximum levels that were maintained through 2003-2004, and declined to slightly below mean levels during 2005-2007. The differing long-term zooplankton abundance patterns may reflect species-specific zooplankton responses to interannual variation in wind strength and direction as modulated by a large-scale driver of winter weather in this region (the North Atlantic Oscillation; Turner et al 2006, Jiang et al 2007b). …”
Section: Nutrient Patternsmentioning
confidence: 99%
“…However, numerous prior studies suggest that much of the variation in right whale habitat use over timescales of weeks to years in the Gulf of Maine and adjacent regions is driven by the varying distribution of the extremely dense patches of copepod prey that right whales apparently require for energetically profitable feeding (Baumgartner, Cole, Clapham, & Mate, 2003;Baumgartner et al, 2007;Davies et al, 2015;Jiang et al, 2007;Mayo & Marx, 1990;Patrician & Kenney, 2010;Pendleton et al, 2009Pendleton et al, , 2012Pershing et al, 2009). In some studies, physical oceanographic features such as bathymetry, SST, SST gradient, bottom mixed layer depth, salinity profiles, and circulation patterns have been found to be correlated with right whale habitat use, but the influences of these physical factors on whale distribution are probably indirect, via their effects on prey concentration Jiang et al, 2007;Keller et al, 2006;Pendleton et al, 2009Pendleton et al, , 2012Pershing et al, 2009). Other environmental parameters, such as chlorophyll concentration, weakly correlate with right whale calving rates (Hlista, Sosik, Traykovski, Kenney, & Moore, 2009) and habitat suitability (Pendleton et al, 2012).…”
Section: Discussionmentioning
confidence: 99%